FEATURES OF THE OFFICE SPACE DESIGN FOR PEOPLE WITH MUSCULOSKELETAL DISORDERS - Полякова, О. В.; Булгакова, Т. В.; Косенко, Д. Ю.; Шмельова, О. Є.; Марета, О. Є. (Art and Design, 2021)
Purpose. The aim of the work is to identify the design features of office premises for people with musculoskeletal disorders and to determine the main functional groups of the subject content of the environment with universal equipment. Methodology. The study is based on a systemic and environmental approach, which allows considering the interior space of office premises and specialized equipment for people with musculoskeletal disorders as a hierarchically subordinate entity. The source base of the research were scientific and journalistic articles, domestic and foreign project developments of office spaces, catalogs of office furniture and equipment. Results. We analyzed the research base on the problems of organizing an office environment for people with disabilities and disorders of the musculoskeletal system. Based on a systematic approach, we analyzed modern office spaces for the possibility of applying the principles of universal design when creating the design of a modern working environment, which will provide equal working opportunities for people with chronic disabilities and will ensure the prevention of diseases of the musculoskeletal system of workers. We have developed a structural model of universal interior office space in order to further expand and refine it, anticipate the development of technologies, equipment and design solutions, improve the working conditions of all employees. We analyzed the main functional groups of office filling with furniture and equipment in terms of their ability to facilitate the use of people with musculoskeletal disorders, as well as the prevention of such diseases in other workers. The right combination of universal and special equipment for all functional groups of the office environment will create a space that is comfortable for the work of different people, it will ensure the maintenance of health and the prevention of diseases associated with static loads of a sedentary way of working. Scientific novelty. We formed the design model structure for the interior environment of office premises for people with disabilities of the musculoskeletal system. Practical significance of the study is determined by the expansion and deepening of knowledge about the formation of the design of office environments and filling them with equipment that provides the possibility of comfortable work for people with musculoskeletal disorders and can be used in the practice of designing appropriate environments.